2022 Global food report on food crises: Joint analysis for better decisions: Mid-year update - Food Security Information Network; Vos, Rob; Rice, Brendan; Minot, Nicholas (Food and Agriculture Organization of the United Nations, 2022)
According to the GRFC 2022 Mid-Year Update, the number of people in Crisis or worse (IPC/CH Phase 3 or above) or equivalent – that is the number of people requiring urgent humanitarian assistance – is forecast to reach up to 205.1 million in 45 of the 53 countries/territories included in the GRFC 2022, published in May 2022. This number includes 14 new or updated 2022 peak estimates that were released since the publication of the annual report. For the majority of these estimates, the number of people facing Crisis or worse (IPC/CH Phase 3 or above) or equivalent has been revised upwards since 2021. For these 45 countries/territories, the data included in this GRFC 2022 Mid-Year Update represents an increase of up to 29.5 million people between 2021 and 2022 despite many populations in food crisis receiving humanitarian and development assistance, suggesting that needs continue to surpass current support and capacities. This increase must be interpreted with care, given that it can be attributed to both a worsening acute food insecurity situation and an expansion in the population analysed (12 percent) between 2021 and 2022. However, even when considering the share of the analysed population in Crisis or worse (IPC/CH Phase 3 or above) or equivalent, the proportion of the population in these phases has increased in 2022 compared to 2021. In order to capture the total number of people facing acute food insecurity globally, this Mid-Year Update emphasises the need to continue expanding reliable analyses in a broader set of countries. Of the 53 GRFC 2022 countries/territories with comparable and consensual estimates for 2021, this report provides estimates for 45. This is due to lack of data availability for 2022. Estimates for 2022 were not available for eight countries/territories, including the Syrian Arab Republic, Bangladesh (Cox’s Bazar) and Palestine. If the 2021 figures for these eight were added to the 2022 aggregate estimate, an additional 17.3 million people would be in Crisis or worse (IPC/CH Phase 3 or above) or equivalent in 2022. Additionally, due to the timing of some 2022 analyses, many peak estimates do not capture the compounding impacts of the war in Ukraine. Of the 77 countries/territories identified for inclusion in the GRFC 2022 as potential food crises, 24 were not covered due to lack of consensual and comparable data. For example, acute food insecurity estimates covering countries of concern previously identified in the GRFC 2022, including the Bolivarian Republic of Venezuela, are not included in the aggregate figure of 205.1 million for 2022. This underscores both the need to improve data collection and build consensus on existing analyses so as to build a truly global picture of acute food insecurity. The figures do suggest that the drivers of food crises severely affect food systems at global, regional, national and household levels, leading to increasing numbers of people facing acute food insecurity, particularly poor and vulnerable people. The main drivers of food crises – conflict and insecurity, global and national economic shocks and weather extremes – are continuous and relentless, and compounded by long-term pressures on food systems. The rapid-fire succession of shocks aggravates the severity and magnitude of acute food insecurity. Households in food-crisis contexts cannot recover from one episode before another strikes. Our spotlight on global and domestic food prices (see page 14) shows how the cost of food has been rising steadily since the onset of the COVID-19 pandemic. International food commodity prices were at a ten-year high before the economic shocks of the war in Ukraine. Although prices in international markets for staple foods, such as wheat, maize and vegetable oils have returned to preinvasion levels, consumer food prices remain high and therefore purchasing power is not expected to improve significantly. While many of the analyses on which this Mid-Year Update is based were carried out too early to capture the ripple effects of the war in Ukraine on the global economy, all GRFC partners flagged that the rising costs of energy, inputs, production and trade are likely to have a major impact on coming agricultural seasons: farmers may plant less, produce less, export less and earn less. Risks of civil unrest due to high food prices combined with macroeconomic challenges, such as high unemployment rates, and the rising cost of living have also increased (UN, June 2022). Our spotlight on drought in the Horn of Africa draws attention to at least 18.8 million people in Crisis or worse (IPC Phase 3 or above) or equivalent in drought-affected areas of Ethiopia, Kenya and Somalia in mid-2022, a result of successive poor rainy seasons affecting pastoral and agricultural livelihoods. An estimated 6.1 million children under 5 years are projected to suffer from wasting at some point during the course of 2022 in these three countries, including 1.8 million with severe wasting (FSNWG, July 2022). In mid-2022, the magnitude and severity of acute food insecurity in countries with available data is truly alarming. The countries included in this GRFC 2022 Mid-Year Update require greater humanitarian assistance in 2022 than 2021, as well as medium and long-term resilience building, livelihood protection and disaster risk reduction support. Never has there been a greater need to act together to tackle the root global causes of food crises. The majority of the acute food insecurity estimates included in the GRFC 2022 Mid-Year Update are current analyses or projections from IPC/CH, which identify the highest number of people in Crisis or worse (IPC/CH Phase 3 or above) or equivalent based on available data and the most likely scenarios during a projected period. In countries where an IPC/CH estimate is unavailable, an IPC-compatible estimated range of the number of people in Crisis or worse (IPC Phase 3 or above) is provided by FEWS NET, based on a most-likely scenario in the absence of humanitarian food assistance. Other acute food insecurity data sources employed in this report include WFP estimates, based on the CARI methodology, as well as Humanitarian Need Overviews (HNOs) and Humanitarian Response Plans (HRPs). The report prioritizes the use of IPC and CH as data sources for Crisis or worse (IPC/CH Phase 3 or above) levels of acute food insecurity. When recent IPC/CH data are not available, alternative sources are considered such as FEWS NET or the WFP CARI scale. FEWS NET and IPC use the same scale although FEWS NET figures may differ as it uses a different approach. CARI is an approximation of IPC/CH Phase 3 or above. As a general rule, based on consensus between partners in the framework of the GRFC, populations that are classified as ‘moderately food insecure’ and ‘severely food insecure’ as per WFP CARI methodology are reported as broadly equivalent to populations facing IPC/CH Phase 3 or above. The objective of this report is to update GRFC 2022 acute food insecurity figures. The number and analyses generated for 2022 are based on: • Available 2022 peak estimates that were reported in the GRFC 2022, as well as 14 new or revised peak estimates released between April and August 2022. Between these two sources, 2022 data are available for 45 of the 53 GRFC 2022 food-crisis countries/territories; • Estimates of acute food insecurity within populations and geographical areas covered by IPC/CH, FEWS NET, WFP CARI, HNOs/HRPs, which do not necessarily provide 100 percent population and geographical coverage (see Annex 1); • Population in IPC/CH Phase 3 or above or equivalent – i.e. those in need of urgent humanitarian assistance. All partners agree on the severity and magnitude of acute food insecurity for the countries/territories included in this GRFC 2022 Mid-Year Update. However, for 2022 estimates covering Afghanistan, the Central African Republic, the Democratic Republic of the Congo, Guatemala, Haiti, Nigeria, the Niger, the Sudan and Yemen, FEWS NET produced estimates that were lower than those provided by the IPC Technical Working Groups, the CH and the 2022 Ethiopia Humanitarian Response Plan (HRP) (see Technical Notes). FEWS NET also provided disclaimers for additional countries with 2021 data included in the GRFC 2022 (see Technical Notes). These differences contribute to FEWS NET obtaining a different trend in estimating global needs between 2021 and 2022.